Praktik Ngalak Paron Dalam Perspektif Ekonomi Syariah Di Desa Gunung Sereng Kecamatan Kwanyar Kabupaten Bangkalan - Rifa’i, Rifa’i; Suryaningsih, Sri Abidah (Ecopreneur : Jurnal Ekonomi dan Bisnis Islam, 2023)
Islam is a complete and perfect religion as well. It governs human behavior in everything, including aqidah worship and muamalah. One of the muamalah practices is in terms of profit-sharing cooperation in agriculture. Ngalak Paron is a practice of cooperative production sharing in agriculture between landowners and sharecroppers with revenue sharing according to the agreement of both parties. In practice, Ngalak Paron is the same as a mukhabarah contract, where capital or seeds come from sharecroppers. This research was conducted with the aim of determining whether the practice of Ngalak Paron is in accordance with the Islamic economy. This study used descriptive qualitative research methods, data collection by observation, interviews, and documentation. The results of Ngalak Paron research conducted in Gunung Sereng Village have fulfilled the pillars and requirements of the mukhabarah contract so that the practice of Ngalak Paron carried out is in accordance with Islamic Law, so that the practice of Ngalak Paron using the mukhabarah contract can be carried out.Keywords: Ngalak Paron, Mukhabarah, Islamic Law Abstrak Islam adalah agama yang lengkap dan sempurna juga. Yang mengatur perilaku manusia dalam segala hal, termasuk aqidah, ibadah dan muamalah. Salah satu dari praktik muamalah yaitu dalam hal kerja sama bagi hasil di bidang pertanian. Ngalak Paron merupakan praktik kerjasama bagi hasil dalam pertanian antara pemilik lahan dengan petani penggarap dengan pembagian hasil sesuai kesepakatan kedua belah pihak. Dalam praktiknya Ngalak Paron sama dengan akad mukhabarah, dimana modal atau benih berasal dari petani penggarap. Penelitian ini dilakukan dengan tujuan untuk mengetahui praktik Ngalak Paron apakah telah sesuai dengan ekonomi syariah. Penelitian ini menggunakan metode penelitian kualitatif deskriptif, pengumpulan data dengan cara observasi wawancara dan dokumentasi. Hasil dari penelitian Ngalak Paron yang dilakukan di Desa Gunung Sereng telah memenuhi rukun dan syarat dari akad mukhabarah sehingga praktik Ngalak Paron yang dilakukan telah sesuai dengan Hukum Islam, sehingga praktik Ngalak Paron menggunakan akad mukhabarah boleh dilakukan. Kata Kunci: Ngalak Paron, Mukhabarah, Hukum Islam